(untitled) (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2013)
First of all, the subjective or internal factors-properties causing an action of the right are the properties of the subjects, which consciousness reflects and realizes a regulatory reality. The properties are a high-quality manifestation of subjectivity and subjectivity of a person at her introduction in the public relations. A subjectivity means a potential possibility of a person to act with the subject of the public relations including legal relations. A subjectivity means that a person estimates surrounding reality subjectively, from own world outlooks.